L-Selectin Enhanced T Cells Improve the Efficacy of Cancer Immunotherapy - Watson, H. Angharad; Durairaj, Ruban R. P.; Ohme, Julia; Alatsatianos, Markella; Almutairi, Hanan; Mohammed, Rebar N.; Vigar, Miriam; Reed, Sophie G.; Paisey, Stephen J.; Marshall, Christopher; Gallimore, Awen; Ager, Ann (Frontiers in Immunology, 2019)
The T cell homing molecule, L-selectin (CD62L), is commonly used as a marker of T cell activation, as expression of L-selectin is downregulated following engagement of the T cell receptor. Furthermore, it is used to distinguish “central memory” T cells (TCM) from, “effector memory” T cells (TEM). It has been reported that CD8+ T cells with a CD62L+ TCM phenotype are better able to control tumour growth than CD62L- TEM CD8+ T cells, while L-selectin knockout T cells are poor at controlling tumour growth. Here, we test the hypothesis that T cells expressing a genetically modified form of L-selectin that is not downregulated following T cell activation (L-selectin enhanced T cells) are better able to control tumour growth than wild type T cells. Using mouse models of solid and disseminated tumours, we show that L-selectin enhancement improves the efficacy of CD8+ T cells in controlling tumour growth. Longitudinal tracking of Zirconium-89 (89Zr) labelled T cells using PET-CT showed that transferred T cells localised to tumours within 24 hours. Early T cell recruitment into tumours was not dependent on L-selectin, however, upregulation of the early activation marker CD69 was higher on L-selectin expressing T cells both inside tumours and in secondary lymphoid organs. Reduced growth of tumours by L-selectin enhanced T cells correlated with increased frequency of CD8+ tumour infiltrating T cells 21 days after commencing therapy. Ex vivo analysis showed that clonal expansion of L-selectin enhanced T cells was slower, and that L-selectin was linked to expression of the proliferation marker Ki67. Together these findings indicate that maintaining L-selectin expression on tumour-specific T cells offers an advantage in mouse models of cancer immunotherapy. The beneficial role of L-selectin may be unrelated to its’ well-known role in T cell homing and instead linked to activation, clonal expansion and retention of therapeutic T cells. These findings have implications both for the selection of T cell subsets for adoptive transfer immunotherapy, and for possible modifications of transgenic chimeric antigen receptor (CAR) T cells to broaden the clinical scope of these therapies.